FARMERS' PREFERENCE FOR RICE TRAITS: INSIGHTS FROM FARM SURVEYS IN BUSIA COUNTY, KENYA - Danda, Kengo; Kimani, John; Ho Kang, Kyung (International Journal of Agriculture, 2022)
Purpose: A cross-sectional survey was designed to study farmers' preferences for rice varieties in Busia County, Kenya. Methodology: The survey used a multi-stage sampling technique for site selection and a purposive strategy for rice growers/producers. Data was collected from key rice value chain stakeholders including farmers, extension service providers, local leaders and hoteliers using focus group discussions by use of guiding checklists and a structured questionnaire. A total of 26 key informants and 62 individual respondents in the categories mentioned were interviewed. Descriptive analysis was done along with cross-tabulations to establish associations. Findings: Results indicated that rice was a significantly important farm enterprise among the respondents with a higher land allocation of 2.04 acres followed by maize with 1.14 acres. Seed sources were mainly traditional with fellow farmers being instrumental in seed sharing at cost (59.7% buying form other farmers) followed by free issues (19.4% getting free from other farmers). Research as a seed source lagged at 8.1%. Variety choice was said to be dictated by high yield, early maturity and one thousand seed weight by 80.6%, 77.4% and 40.3% respectively. These attributes were also ranked as first, second and third positions respectively. Rice production followed traditional patterns as 60% of producers/farmers depended on a farmer-to-farmer seed system over all the production periods. There also lacked structures and efforts to upscale rice production and therefore this paper recommends formulation and direction of concerted efforts towards on-farm participatory research and formation of social networks for rice production and marketing information Contribution to theory, practice and policy: The results give impetus to conclude that farmers know which traits are of priority in variety selection. Going by farmers' perceptions simply means responding to consumer demand for quality in rice production. The study also demonstrated enormous potential for rice production as demonstrated by the will of the farmers to allocate 45% of their land parcels to rice production. It also brought out that the fact that certified rice seeds are rarely used and therefore, there is urgent need to establish seed systems and distribution pathways in order to improve on yields as well as quality of paddy hence more income to farmers and other rice value chain players. The concepts of field demonstrations and on-farm participatory research need to be up-scaling for enhanced transformation of rice production landscape in the region.